Effect of efficiency, effectiveness, regional financial independence and local government service capacity on regional economic growth - Maya Dian Indah Sari (Indonesia Accounting Research Journal, 2021)
This study aims to determine the effect of efficiency, effectiveness, regional financial independence and local government service capacity on regional economic growth in districts and cities in the province. The population in this study is the regional government of Central Java province, totaling 35 regencies and cities. The sampling method uses the census method where the entire population is taken as research data, namely reports on the realization of regional government budgets throughout Central Java Province for 4 consecutive years, namely 2008-2011. Analysis using multiple linear regression. The results of this study indicate that efficiency, effectiveness, regional financial independence and local government service capacity simultaneously influence regional economic growth. This is indicated by the F count of 11.4346 and the F table of 2.4387. So that F count > F table. Partially, it is known that the efficiency variable has no effect on regional economic growth with a t count < t table or 0.3352 < 1.9777, for the effectiveness variable has an effect on economic growth with t count > t table or 2.4884 > 1, 9777, the regional financial independence variable affects regional economic growth with t count > t table or 4.5884 > 1.9777, and local government service capacity influences regional economic growth with t count > t table or 2.0683 > 1, 9777.